2021
DOI: 10.1099/mgen.0.000579
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the acquisition of the pks island and production of colibactin in the Escherichia coli population

Abstract: The pks island codes for the enzymes necessary for synthesis of the genotoxin colibactin, which contributes to the virulence of Escherichia coli strains and is suspected of promoting colorectal cancer. From a collection of 785 human and bovine E. coli isolates, we identified 109 strains carrying a highly conserved pks island, mostly from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Colibactin may induce DNA damage in the host and has been correlated with colorectal cancer in humans (Wernke et al, 2020). Previous studies have confirmed the presence of pks-positive strains among ExPEC (Auvray et al, 2021). Interestingly, 75 of our isolates (19.9%) were colibactin-encoding strains, a higher percentage than this observed by Suresh et al (2018).…”
Section: Discussionsupporting
confidence: 57%
“…Colibactin may induce DNA damage in the host and has been correlated with colorectal cancer in humans (Wernke et al, 2020). Previous studies have confirmed the presence of pks-positive strains among ExPEC (Auvray et al, 2021). Interestingly, 75 of our isolates (19.9%) were colibactin-encoding strains, a higher percentage than this observed by Suresh et al (2018).…”
Section: Discussionsupporting
confidence: 57%
“…Although HPI is not self-transferable, comparative genomic analyses and conjugation experiments indicated that joint horizontal transfer of the HPI can occur along with the pks island and another adjacent chromosomal island ( 59 ). In other colibactin-producing coliform enterobacteria, such as Klebsiella pneumoniae , Citrobacter koseri , and Klebsiella (formerly Enterobacter ) aerogenes , the colibactin and yersiniabactin determinants are colocalized within an integrative and conjugative element (ICE) ( 1 3 ), confirming that physical linkage of the colibactin and yersiniabactin islands is actively supported by joint acquisition or spread via horizontal gene transfer.…”
Section: Discussionmentioning
confidence: 90%
“…A variety of Escherichia coli strains belonging to the phylogenetic group B2, which comprises extraintestinal pathogenic E. coli (ExPEC) as well as commensal E. coli strains, have been identified to carry two potentially linked genomic islands, namely, the so-called “high pathogenicity island” (HPI) and the polyketide synthase ( pks ) island. Both islands are chromosomally located in close proximity, and the pks island always coexists with the HPI ( 1 3 ). Each island carries all necessary genes for a combined polyketide synthase (PKS) and nonribosomal peptide synthase (NRPS) biosynthesis machinery, producing either colibactin or yersiniabactin.…”
Section: Introductionmentioning
confidence: 99%
“…E. coli group B2 includes commensal strains and pathogenic strains that are responsible for extra-intestinal diseases, including urinary tract infections, sepsis, pneumonia, and neonatal meningitis. Among the strains of the B2 phylogroup, there are a large number of strains that possess in their genome the pks island that encodes the genotoxin colibactin [3,4]. These pks + strains of E. coli are frequently found in asymptomatic carriage in the digestive tract from the first days after birth [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The pks island encoding enzymes responsible for colibactin biosynthesis is mainly present in this group. The sequence of the pks island is highly conserved and pks-carrying (pks + ) strains are found overwhelmingly capable to produce colibactin [3]. The biosynthesis of colibactin has been summarized in two nice reviews [8,9].…”
Section: Introductionmentioning
confidence: 99%